Critical numbers of attractive Bose-Einstein condensed atoms in asymmetric traps - Gammal, A.; Tomio, Lauro [UNESP]; Frederico, T. (American Physical Society (APS), 2002)
The recent Bose-Einstein condensation of ultracold atoms with attractive interactions led us to consider the possibility of probing the stability of its ground state in arbitrary three-dimensional harmonic traps. We performed a quantitative analysis of the critical number of atoms through a full numerical solution of the mean-field Gross-Pitaevskii equation. Characteristic limits are obtained for reductions from three to two and one dimensions, in perfect cylindrical symmetries as well as in deformed ones. 5555 2002 The American Physical Society.